INDIRECT WRITTEN CORRECTIVE FEEDBACK, REVISION, AND LEARNING - Poorebrahim, Fatemeh (Indonesian Journal of Applied Linguistics, 2017)
Corrective feedback, the necessity of providing it, and how it should be provided has been one of the hot topics in the area of ELT. Amid continuing controversies over whether providing feedback helps L2 learners improve their writing accuracy, many research studies have been undertaken to compare the relative effectiveness of different types of feedback. However, the difference between two types of indirect corrective feedback, namely indication and indication plus location, have not been properly examined yet. Motivated to narrow this gap, this study is designed to compare two groups of Iranian learners, each revising their papers based on one of the aforementioned options. For data analysis, a series of independent samples t tests were employed. The results revealed that the difference between the two groups in their reduction of errors from the original draft to the revision of each task followed a growing trend and became significant. Nonetheless, the difference in accuracy of new pieces of writing fell short of significance. Finally, it was found that error reduction in revision stage cannot be considered as learning. The results of the study, discussed in relation to that of others, implicate that the purpose for which feedback is provided is essential in determining the type of feedback; more explicit feedback is better for revising purposes while more implicit feedback is good for learning purposes.